95.7k views
5 votes
- 2(x + 3) + 2(x + 4) = 24​

User Ben Hull
by
5.0k points

2 Answers

3 votes

Answer:

NO SOLUTION

Explanation:


-2(x+3)+2(x+4)=24\qquad\text{use the distributive property}\ a(b+c)=ab+ac\\\\(-2)(x)+(-2)(3)+(2)(x)+(2)(4)=24\\\\-2x-6+2x+8=24\qquad\text{combine like terms}\\\\(-2x+2x)+(-6+8)=24\\\\0+2=24\\\\2=24\qquad\bold{FALSE}\\\\\text{Conclusion:}\\\\\bold{NO\ SOLUTION}

User Valerica
by
5.0k points
1 vote

Answer: no solution

Explanation:

First lets simplify

-2(x+3) + 2(x+4) = 24

-2x - 6 + 2x + 8 = 24

We can simplify this further by combining like terms

2=24 is the equation we get after combining like terms.

Since 2 is not equal to 24, the answer is no solution.

User Masseyb
by
5.2k points